2022
DOI: 10.3390/catal12070761
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Salt Bridges near the Active Site of Cold-Adapted Proteus mirabilis Lipase on Thermal and Organic Solvent Stabilities

Abstract: Organic solvent-tolerant (OST) enzymes have been discovered in psychrophiles. Cold-adapted OST enzymes exhibit increased conformational flexibility in polar organic solvents resulting from their intrinsically flexible structures. Proteus mirabilis lipase (PML), a cold-adapted OST lipase, was used to assess the contribution of salt bridges near the active site involving two arginine residues (R237 and R241) on the helix η1 and an aspartate residue (D248) on the connecting loop to the thermal and organic solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Many studies have identified newly formed salt bridges in lipase variants with improved organic solvent tolerance [ 122 , 123 , 129 ]. To investigate the contribution of salt bridges near the active site to the stability of Proteus mirabilis lipase (PML) in organic solvents, Dachuri et al [ 130 ] substituted alanine for two arginine residues (R237 and R241) and one aspartate residue (D248) which formed salt bridges near the active site and then evaluated their efficiency in 10–40% ( v / v ) DMSO and 10–40% ( v / v ) methanol. The results showed that the double mutant (R237A/D248A) even lost its activity completely within 1 h in the 40% organic solvent, whereas the wild type had about 80% activity in both 40% ( v / v ) organic solvents.…”
Section: Protein Engineering For Improving the Solvent Tolerance Of L...mentioning
confidence: 99%
“…Many studies have identified newly formed salt bridges in lipase variants with improved organic solvent tolerance [ 122 , 123 , 129 ]. To investigate the contribution of salt bridges near the active site to the stability of Proteus mirabilis lipase (PML) in organic solvents, Dachuri et al [ 130 ] substituted alanine for two arginine residues (R237 and R241) and one aspartate residue (D248) which formed salt bridges near the active site and then evaluated their efficiency in 10–40% ( v / v ) DMSO and 10–40% ( v / v ) methanol. The results showed that the double mutant (R237A/D248A) even lost its activity completely within 1 h in the 40% organic solvent, whereas the wild type had about 80% activity in both 40% ( v / v ) organic solvents.…”
Section: Protein Engineering For Improving the Solvent Tolerance Of L...mentioning
confidence: 99%